Factores de riesgo para infección nosocomial en pacientes con trauma, Medellín, 2000 (2003)
ABSTRACT: With the purpose of identify the risk factors for nosocomial infection in patients with trauma, a case control study was conducted in the Pablo Tobón Uribe Hospital of Medellín, between January and December of 1999. The sample included 540 hospitalized patients: 185 infection cases and 355 controls. The information was collected through clinical records and the severity was evaluated using the Injury Severity Score (ISS). After a vicariate analysis, those variables with statistical significance were include in the multivariate analysis. 74.6% of patients were men, with an average age of 33 years. In conclusion there are risk factors for nosocomial infection in patients with trauma related to the host and to the trauma that can be modified, and other factors related to the hospital service that are susceptible of modification. Among them the use of antibiotics, time with nasogastric and peripheral venous catheter and endurance of surfery are the most protruding.